2021
DOI: 10.1002/smll.202107137
|View full text |Cite
|
Sign up to set email alerts
|

Healing Diabetic Ulcers with MoO3−X Nanodots Possessing Intrinsic ROS‐Scavenging and Bacteria‐Killing Capacities

Abstract: neutrophils in the ulcer area can produce excessive reactive oxygen species (ROS) which on one hand injury the epithelial cells to impede the wound recovery, and on the other hand block the supply of oxygen and nutrition to the ulcer area to hinder the angiogenesis. [2] In addition, the high level ROS can induce excessive inflammatory response of the macrophages, enhancing the wound vulnerability that further delays the recovery of DUs. [3] Moreover, the long-term open ulcers are more susceptible to pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…And in diabetic chronic wounds, high levels of glycation end products (AGEs) and an abnormal immune system may induce immune cells such as neutrophils to produce excess ROS (including superoxide anion, hydrogen peroxide, hydroxyl radicals, etc. ), 37 resulting in irreversible cell damage and poor angiogenesis. 23,38 Therefore, the feature to control inflammation is very important for wound dressings, and the strategies to suppress the long-term inflammatory response at the wound site are effective in improving the healing rate of chronic wounds.…”
Section: Anti-inflammatory/antioxidant Activitiesmentioning
confidence: 99%
“…And in diabetic chronic wounds, high levels of glycation end products (AGEs) and an abnormal immune system may induce immune cells such as neutrophils to produce excess ROS (including superoxide anion, hydrogen peroxide, hydroxyl radicals, etc. ), 37 resulting in irreversible cell damage and poor angiogenesis. 23,38 Therefore, the feature to control inflammation is very important for wound dressings, and the strategies to suppress the long-term inflammatory response at the wound site are effective in improving the healing rate of chronic wounds.…”
Section: Anti-inflammatory/antioxidant Activitiesmentioning
confidence: 99%
“…3A). 62 Electron paramagnetic resonance spectral assay indicated that MoO 3−X could scavenge superoxide anions ( • O 2− ), hydroxyl radicals ( • OH), and hydrogen peroxide (H 2 O 2 ). Plate count results indicated that MoO 3−X could inactivate Gram-negative and Gram-positive pathogens, for example, Escherichia coli and Staphylococcus aureus.…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…[2] During traditional monotherapy, inflammation response, bacterial colonization, and microvascular dysfunction often result in the deceleration and even failure of chronic wound healing. [3][4][5] Besides, the occurrence of undesirable side effects and the appearance of drug-resistant bacteria are also depleting the existent drug library. Considering the complicated etiological factors of the injured tissue microenvironment, combination of two or more medicines with nontoxicities and different therapeutic functions are critical steps for successful management of chronic wound regeneration.…”
Section: Introductionmentioning
confidence: 99%